Pentingnya Financial Education dan Financial Knowledge terhadap Inklusi Keuangan Pada Era Fintech di Indonesia - Mega Arisia Dewi (Politeknik Ganesha Medan, 2022)
This study aims to determine the effect of financial literacy (financial education) and (financial knowledge) on financial inclusion in the fintech era in Indonesia and the effect of financial literacy (financial education) and (financial knowledge) on financial inclusion through the Fintech era in Indonesia. This research is a quantitative research. The population of this research is people throughout East Java. The sampling technique used was purposive sampling. The data collection technique of this research used literature study, and field research. This study uses the dependent variable, namely financial inclusion, while the independent variable, namely financial education and financial knowledge, while the moderating variable is financial technology. The conclusion of this study is that the financial education and financial knowledge variables have a negative effect on financial inclusion, while the fintech variable is able to mediate the strong influence of financial education and financial knowledge on financial inclusion. The results of this study provide an opportunity for other researchers to test the effectiveness of various financial inclusion strategies carried out by the government and universities in Indonesia, so as to obtain updated data for further updates.